MASALAH RAWAN DALAM HUBUNGAN INDUSTRIAL DAN KONSEP NEGARA KESEJAHTERAAN INDONESIA - Ahmad Hunaeni Zulkarnaen (Universitas Suryakancana, 2016)
The Indonesian’s Development goal is to achieve national stability, including economical stability, the achievement of nationally economical stability, determined by the stability in the sector of production of goods and services, or its stability in the sector of production of goods and services is the supporting factor to the dominant of national development programs especially economic development program. One of the requirements to achieve stability in the sectoral production of goods and services is the condition of harmonious industrial relations based on Pancasila in the form of peaceful in working situation or industrial peace, is a dynamic condition in working, where there 3 (three) important elements: first the guarantee implementation on rights and obligations; second, conflict can be resolved internally; third, strikes and lockouts (lock-out) should not be used to impose willingness, because conflict could have been resolved well. In fact, in creating a harmonious industrial relations is not easy, there are some contributing factors such as; workers / laborers factor, employers factor, and public administration factor.Keywords: Industrial Relationship Problem, Indonesian Welfare State Concept